Філософські горизонти сучасної нейронауки - Утюж, Ірина Геннадіївна; Сайтарли, І. А.; Utiuzh, I. G.; Sajtarly, I. A. (My University, 2023)
У статті презентується міждисциплінарний дискурс розуміння соціогенези особистості саме з погляду нейронауки, яка значною мірою співзвучна найгучнішим соціально- філософським проектам сучасності. Йдеться, насамперед, про теорії, які концептуально та ідейно відображають тенденції суспільства постмодерну, тобто пов’язані із загальним розумінням значення детермінант суспільного виробництва для "збереження", відтак, відтворення існуючого суспільного устрою. Означений міждисциплінарний дискурс знаходить свою методологічну основу в структуралізмі, особливо у постструктуралізмі, представники якого переконливо доводять кореляцію основних моделей орієнтації особистості та соціальної системи, а нейронауковий дискурс допомогає краще зрозуміти біологічні корені психічного функціонування людини. Така кореляція спостерігається у формуванні афективно- мотиваційної структури особистості, що доводиться низкою широко знаних науковців у галузі соціальної філософії, зокрема представниками психоаналітичної та структуралістської парадигм. Звернення до напрацювань у царині нейронаукового дискурсу, дозволить сформувати нову епістемологічну основу концепцій соціогенези особистості, особливо у контексті проявів її агресивності. This article is the interdisciplinary discourse in regard to the issue of sociogenesis of the personality, mainly, in terms of contemporary neuroscience, which, in a certain sense, is in tune with the most known socio-philosophical treatises on modernity. It refers, primarily, to theories, which conceptually and ideally reflect the main tendencies of postmodern society, put it in another words, which is associated with the general comprehending of the significance of social production determinants on behalf of "conservation", and hence, the reproduction of the established social order. The above interdisciplinary discourse finds its methodological basis in structuralism, especially in poststructuralism, representatives of which convincingly prove the existence of correlation between basic patterns of personal orientation and social system, and neuroscientific discourse helps us to better grasp the biological roots of human psychic functioning. The same correlation can be observed in the desiring affective-motivational structure of personality, that a number of well-known scientists in the field of social philosophy has also substantiated, in particular, the representatives of psychoanalysis and poststructuralism. Reference to explorations in the field of neuroscientific discourse will allow us to formulate a new epistemological basis for conception of sociogenesis of the personality, especially, in regard to aggressive impulses. That is why, this article is aimed at substantiating the necessary to take into account the new discoveries in the field of neurosciences and philosophy, that will enable philosophical theory to conceptualize the idea of sociogenesis of human "passions" and find out verifications of both the idea of social nature of human being and the statement about biological basis of sociality, which have been needed for a long time. The general logic and arguments in favor of interdisciplinary determinism allow us to formulate a new theory of personality, sociogenesis, in which the biological and social manifest in what way the brain and body interact to create and maintain established social relations, while philosophy gives these investigations a conceptual form and essential worldview conclusions.
Philosophical horizons of contemporary neuroscience
Keywords: нейронаука; філософія; соціогенез; теорія особистості; мотиваційно-емоційна система; афективна нейронаука; нейроекзистенціалізм; Neuroscience; Philosophy; Sociogenesis; Personality Theory; Motivational-Emotional System; Affective Neuroscience; Neuro-Existentialism